2019
DOI: 10.3390/nu11020272
|View full text |Cite
|
Sign up to set email alerts
|

UP1306: A Composition Containing Standardized Extracts of Acacia catechu and Morus alba for Arthritis Management

Abstract: Osteoarthritis (OA) is characterized by progressive articular cartilage degradation. Although there have been significant advances in OA management, to date, there are no effective treatment options to modify progression of the disease. We believe these unmet needs could be bridged by nutrients from natural products. Collagen induced arthritis in rats was developed and utilized to evaluate anti-inflammatory and cartilage protection activity of orally administered botanical composition, UP1306 (50 mg/kg) and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Furthermore, moracin, a flavonoid from Mores alba root bark protects against IL-1β-induced osteoarthritis by reducing inflammatory factors (TNF-α, IL-6, and COX2) via attenuating the NF-κB pathway [ 37 ]. Consistent with previous studies [ 35 , 36 , 37 ], the present study also demonstrated that MBW attenuated pain and proinflammatory activities in the articular cartilage along with preventing the reduction of serum testosterone concentrations in the testosterone-deficient rats with MIA-induced osteoarthritis. MBW inhibited the BMD loss only in the leg with osteoarthritis, and it was associated with the suppression of osteoarthritis progression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, moracin, a flavonoid from Mores alba root bark protects against IL-1β-induced osteoarthritis by reducing inflammatory factors (TNF-α, IL-6, and COX2) via attenuating the NF-κB pathway [ 37 ]. Consistent with previous studies [ 35 , 36 , 37 ], the present study also demonstrated that MBW attenuated pain and proinflammatory activities in the articular cartilage along with preventing the reduction of serum testosterone concentrations in the testosterone-deficient rats with MIA-induced osteoarthritis. MBW inhibited the BMD loss only in the leg with osteoarthritis, and it was associated with the suppression of osteoarthritis progression.…”
Section: Discussionsupporting
confidence: 92%
“…It is also reported to facilitate weight loss by suppressing appetite and improving dyslipidemia [ 33 , 34 ]. Oral intake of a mixture of Acacia catechu water extract and Morus alba root bark ethanol extract (50 mg/kg BW) has anti-inflammatory (TNF-α and IL-1β), collagenase (MMP-13) inhibitory, and articular cartilage protective activities in MIA-induced arthritis [ 35 , 36 ]. Furthermore, moracin, a flavonoid from Mores alba root bark protects against IL-1β-induced osteoarthritis by reducing inflammatory factors (TNF-α, IL-6, and COX2) via attenuating the NF-κB pathway [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, pain, or mechanical injury may result in an abnormal gait characterized by limping and lameness (Ross & Dyson, 2011). The proinflammatory cytokines IL‐1β and TNF‐α also reduce anabolic processes in chondrocytes, thus decreasing the synthesis of extracellular matrix components (Yimam et al., 2019).…”
Section: Discussionmentioning
confidence: 99%